2013
DOI: 10.18632/oncotarget.1444
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the biological impact of CDKN2A and MC1R genes as an early predisposing event in melanoma and non melanoma skin cancer

Abstract: Germline mutations in CDKN2A and/or red hair color variants in MC1R genes are associated with an increased susceptibility to develop cutaneous melanoma or non melanoma skin cancer.We studied the impact of the CDKN2A germinal mutation p.G101W and MC1R variants on gene expression and transcription profiles associated with skin cancer. To this end we set-up primary skin cell co-cultures from siblings of melanoma prone-families that were later analyzed using the expression array approach.As a result, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 75 publications
1
35
0
Order By: Relevance
“…IFI44L is reported upregulated in human nasopharyngeal carcinoma cells modulated through the downregulation of miR-9 [ 37 ]. In melanoma and non-melanoma skin cancer cells with CDKN2A mutated, IFI44L is also reported upregulated [ 38 ]. However these finding remains at the level of cell biology and none evident was reported that the deregulation of IFI44L may influence the progression or prognosis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…IFI44L is reported upregulated in human nasopharyngeal carcinoma cells modulated through the downregulation of miR-9 [ 37 ]. In melanoma and non-melanoma skin cancer cells with CDKN2A mutated, IFI44L is also reported upregulated [ 38 ]. However these finding remains at the level of cell biology and none evident was reported that the deregulation of IFI44L may influence the progression or prognosis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also implicated a potential role of general pigmentation in PD. For example, primary skin cultures from individuals with red hair color showed deregulation of genes involved in neurodegenerative diseases such as PD . A clinical study reported a correlation between light pigmentation phenotype and increased echogenicity of the substantia nigra .…”
Section: Discussionmentioning
confidence: 99%
“…The transition from the radial growth phase to the vertical growth phase is responsible for the majority of cancer-associated mortalities caused by melanoma (2). Sun exposure and acquired genetic alterations are two well-established etiologies for melanoma, and previous studies have revealed that congenital germline mutation of certain critical genes, such as cyclin-dependent kinase inhibitor 2A, is another risk factor (3)(4)(5). The diagnostic technology and health consciousness regarding melanoma have greatly improved in recent years and, furthermore, the surgical techniques and adjuvant treatment measures have progressed (6,7).…”
Section: Introductionmentioning
confidence: 99%